In vivo evaluation of pharmacokinetic drug–drug interactions between fluorinated pyrimidine anticancer drugs, 5-fluorouracil and capecitabin, and an anticoagulant, warfarin. (3rd June 2022) - Hasegawa, Ai; Tsujiya, Yoshie; Ueda, Ayaka; Yamamori, Motohiro; Okamura, Noboru
Abstract: Warfarin is a common anticoagulant and has demonstrated interactions with several drugs. Among them, as a serious adverse event, a case of death due to the enhanced warfarin action owing to its combined use with a fluoropyrimidine anticancer drug has been reported, but the detailed mechanism has not been elucidated. Some reports have advocated that fluorinated pyrimidine anticancer drugs reduce cytochrome P450 2C9 expression, leading to the enhanced pharmacological effects of warfarin. The purpose of this study was to clarify the mechanisms of drug–drug interactions between warfarin and 5-fluorouracil (5-FU) and capecitabine in vivo using rats. Rats were administered warfarin in combination with 5-FU (15 mg/kg/d) or capecitabine (15 mg/kg/d) for 7 d. Prothrombin time (PT) and activated partial thromboplastin time were significantly prolonged in the warfarin plus 5-FU or capecitabine groups compared with those in the warfarin alone group. No significant difference was observed in the area under the plasma concentration-time curve of the warfarin alone group compared with the warfarin with 5-FU or capecitabine groups. These data suggest that the enhancement of warfarin efficacy caused by the combination of 5-FU or capecitabine was due to a pharmacological interaction rather than a pharmacokinetic interaction.